The dietetics leadership identity project: leadership taxonomy in clinical dietetics - Patten, Emily Vaterlaus (Kansas State University, 2016)
There has been a historic and consistent call for Registered Dietitian Nutritionists (RDN) to develop and practice leadership skills regardless of roles and responsibilities. The majority of RDNs practice as clinicians in the health care environment, however, there is no clear description of what leadership entails in that setting. Very little published research exists regarding leadership in dietetics, and there are no known studies about clinical leadership in the profession. The purpose of this exploratory study was to develop an evidence and practice-based leadership behavior taxonomy for clinical RDNs. To do this, a comprehensive list of leadership behavior items was developed based on literature review and then validated by an expert panel of Clinical Nutrition Managers. A stratified random national sample of 4,700 clinical RDNs was invited to complete the survey instrument; participants rated the frequency of demonstrating each behavior item and the potential benefit to the patients or clients if they demonstrated it. Additional questions exploring clinical RDNs’ experiences and perspectives of clinical leadership and demographics were asked. There was a 14.6% response rate (N = 684). The frequency data were used to conduct exploratory (EFA) and confirmatory factor analyses. Five factors emerged from the EFA and a clinical leadership behavior taxonomy was developed based on those findings. Most clinical RDNs considered themselves clinical leaders (74.9%), felt that leadership was relevant to daily clinical nutrition practice (89.6%), and enjoyed their jobs more when practicing leadership at work (75.7%). One-way ANOVAs and independent t tests revealed no significant differences in composite mean leadership frequency scores across gender, level of education, years in practice, years in current position, type of current position, or having a specialty certification, however, there was a significant relationship between composite scores and levels of professional involvement Welch’s F (3, 674) = 13.79, p < .001. This research advances clinical dietetics practice by creating a common language to discuss leadership and its development and practice, the taxonomy should inform education standards, continuing education offerings, and employee development for clinical RDNs.
Keywords: Clinical leadership; Dietetics leadership; Clinical dietetics; Leadership taxonomy